Oncology and infertility: selected issues. Part II. Preservation of the reproductive function - Mazur-Roszak, Małgorzata; Tomczak, Piotr; Litwiniuk, Maria; Markowska, Janina (Contemporary Oncology/Współczesna Onkologia, 2005)
Recent years have witnessed an increase in oncological patients at the reproductive age. Consequently, the protection of their fertility has become an important issue. Male patients who are to undergo chemo- or radiotherapy are advised about the possibility of having their sperm preserved (cryopreservation). Frozen sperm may be later used for artificial insemination or fertilization using one of the assisted reproductive technologies such as in vitro fertilization, gamete intrafallopian transfer, zygote intrafallopian transfer, or intracytoplasmatic injection. A pioneer method here is the transplantation of the patients testis tissue collected and frozen before the treatment. A routine method used in female patients is the cryopreservation of an embryo, while the preservation of oocytes or of the ovarian tissue is still under investigation. There is no evidence of an increased risk of fetal pathology in children of patients who have undergone prior oncological treatment. Most in vitro pregnancies are normal. What is more, available data show no indications that pregnancies after oncological treatment lead to an increased risk of a relapse of the disease. The above findings confirm that there are no grounds for discouraging successful oncological patients from having children. However, since most cancer recurrences appear within two to three years after the initial diagnosis, many oncologists suggest that patients should postpone family planning until after the lapse of that period.